Free-flap reconstruction in early-stage squamous cell carcinoma of the oral cavity - a prospective monocentric trial to evaluate oncological outcome and quality of life - Moratin, Julius; Zittel, Sven; Horn, Dominik; Behnisch, Rouven; Ristow, Oliver; Engel, Michael; Hoffmann, Jürgen; Freier, Kolja; Freudlsperger, Christian (Journal of Clinical Medicine, 2023)
Surgery is generally accepted as standard treatment in oral cancer, but the reconstructive procedures remain a matter of debate. The aim of this study was to evaluate oncological outcome and quality of life following surgical resection and free-flap reconstruction in patients with early oral squamous cell carcinoma. The presented trial was performed as a prospective, single-center observation study. Inclusion criteria were primary surgery in early-stage oral squamous cell carcinoma with free-flap reconstruction. Endpoints were overall and progression-free survival and quality of life up to 24 months after surgery. Twenty-six patients were included. Overall survival was 100% and progression-free survival was 92.3% in a maximum follow-up time of 21 months. Global quality of life showed no significant alteration after surgery. Patients reported a significant reduction in pain (p = 0.048) and a decreasing impairment of speech one year after surgery (p = 0.021). Free-flap reconstruction is a safe procedure that results in excellent oncological outcome and quality of life. Functional outcome is of high relevance in early-stage tumors of the head and neck and may mostly be affected by reconstructive procedures. Therefore, a prospective evaluation to explore success and the effects of surgical therapy is highly warranted.
Veröffentlicht: 22. Juli 2023
Gesehen am 24.08.2023